Aus den Beständen der Galerie : Einladung zur Kunstmesse 21' Art Basel. - Galerie Michael Haas, Berlin (Berlin : Galerie Michael Haas, 1990)
Appel, Karel ; Christo ; Jorn, Asger ; Gottlieb, Adolph ; Hofmann, Hans ; Chaissac, Gaston ; Soutter, Louis
Aus den Beständen der Galerie : Einladung zur Kunstmesse 21' Art Basel, Galerie Michael Haas, Berlin, 1990
boek